2019
DOI: 10.3390/su11030775
|View full text |Cite
|
Sign up to set email alerts
|

Post-1990s College Students Academic Sustainability: The Role of Negative Emotions, Achievement Goals, and Self-efficacy on Academic Performance

Abstract: In 1982, the “one-child policy” was implemented by China’s Constitution, which led to the majority of post-1990s college students in China being the only child in their family. Unique characteristics have been demonstrated in psychological development of post-1990s Chinese college students due to the lack of sibling companionship, and the relationship between their psychological state and academic performance can affect their future academic sustainability. This paper used Beijing College Students Panel Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…Participants of the survey were randomly chosen from students admitted to 15 universities in the years of 2006 and 2008, and these two cohorts were tracked for four consecutive years from June 2009 to June 2012. The first three rounds were carried out on-site with the cooperation of Beijing Municipal Commission of Education and the Office of Student Affairs of the universities; thereafter, in year four, the participants were invited via text messages and e-mails to log in to the questionnaire website with a unique code, and this round of investigation was conducted entirely online [41]. In order to explore changes in students’ mental health states across years during college, the 2008 cohort was selected and analyzed in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants of the survey were randomly chosen from students admitted to 15 universities in the years of 2006 and 2008, and these two cohorts were tracked for four consecutive years from June 2009 to June 2012. The first three rounds were carried out on-site with the cooperation of Beijing Municipal Commission of Education and the Office of Student Affairs of the universities; thereafter, in year four, the participants were invited via text messages and e-mails to log in to the questionnaire website with a unique code, and this round of investigation was conducted entirely online [41]. In order to explore changes in students’ mental health states across years during college, the 2008 cohort was selected and analyzed in our study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to explore changes in students’ mental health states across years during college, the 2008 cohort was selected and analyzed in our study. The initial numbers of participants from different universities in the first round have been listed in Table 1, and the follow-up rate of the latter three rounds was 95.27%, 94.66%, and 90.58%, respectively, with very few sample losses [41]. After removing invalid questionnaires, the effective sample size of this panel study was 1401, including 650 females and 751 males.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy and empathy are two constructs that directly influence academic performance and social interaction [4][5][6][7]. Self-efficacy, in the academic field, is understood as the student's belief in their abilities to undertake those activities that are required of them in the educational context [8,9].…”
Section: Perceived Academic Self-efficacymentioning
confidence: 99%
“…Previous studies have suggested that high selfefficacy may be associated with better academic performance [45][46][47][48]. For example, a study of undergraduates at Cornell University by Ballen et al found that self-efficacy could drive their performance gains with active learning [45].…”
Section: Discussionmentioning
confidence: 99%